Root hydrotropism is controlled via a cortex-specific growth mechanism - Dietrich, Daniela; Pang, Lei; Kobayashi, Akie; Fozard, John A.; Boudolf, Véronique; Bhosale, Rahul; Antoni, Regina; Nguyen, Tuan; Hiratsuka, Sotaro; Fujii, Nobuharu; Miyazawa, Yutaka; Bae, Tae-Woong; et al. (Nature Publishing Group, 2017)
Plants can acclimate by using tropisms to link the direction of growth to environmental conditions. Hydrotropism allows roots to forage for water, a process known to depend on abscisic acid (ABA) but whose molecular and cellular basis remains unclear. Here, we show that hydrotropism still occurs in roots after laser ablation removed the meristem and root cap. Additionally, targeted expression studies reveal that hydrotropism depends on the ABA signalling kinase, SnRK2.2, and the hydrotropism-specific MIZ1, both acting specifically in elongation zone cortical cells. Conversely, hydrotropism, but not gravitropism, is inhibited by preventing differential cell-length increases in the cortex, but not in other cell types. We conclude that root tropic responses to gravity and water are driven by distinct tissue-based mechanisms. In addition, unlike its role in root gravitropism, the elongation zone performs a dual function during a hydrotropic response, both sensing a water potential gradient and subsequently undergoing differential growth.